2021
DOI: 10.3389/fpsyt.2021.641102
|View full text |Cite
|
Sign up to set email alerts
|

Couple Relationships Are Associated With Increased REM Sleep—A Proof-of-Concept Analysis of a Large Dataset Using Ambulatory Polysomnography

Abstract: Background/Objectives: Rapid Eye Movement (REM) sleep is associated with memory consolidation and several health effects including stress response, mental health, and longevity. Recently, it has been shown that regularly co-sleeping couples have increased and stabilized REM sleep when co-sleeping as compared to sleeping individually. However, it remained unclear whether this is due to a specific effect of altering the usual sleeping environment by partner deprivation or due to a generalizable REM-sleep promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A meta-analysis of observational studies has attested that insomnia is more prevalent among women compared to men (23). Moreover, an analysis of sleep and sociodemographic data showed that that (in general) married individuals experienced greater levels of REM (rapid eye movement) sleep compared to non-married individuals (24). In terms of sleep problems, women experience more sleep problems than men, and the results are consistent for divorced and widowed individuals compared to married ones (25).…”
Section: Introductionmentioning
confidence: 98%
“…A meta-analysis of observational studies has attested that insomnia is more prevalent among women compared to men (23). Moreover, an analysis of sleep and sociodemographic data showed that that (in general) married individuals experienced greater levels of REM (rapid eye movement) sleep compared to non-married individuals (24). In terms of sleep problems, women experience more sleep problems than men, and the results are consistent for divorced and widowed individuals compared to married ones (25).…”
Section: Introductionmentioning
confidence: 98%